2017
DOI: 10.1159/000485843
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glycemic Markers in Chronic Hemodialysis Using Continuous Glucose Monitoring

Abstract: Background: Glycated hemoglobin A1c (HbA1c) among diabetic hemodialysis patients continues to be the standard of care, although its limitations are well recognized. This study evaluated glycated albumin (GA) and glycated serum protein (GSP) as alternatives to HbA1c in detecting glycemic control among diabetic hemodialysis patients using continuous-glucose-monitoring (CGM)-derived glucose as reference standard. Methods: A CGM system (iPRO) was applied for 7 days in 37 diabetic hemodialysis patients to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Finally, the measurements that are most important to the patient on a day-by-day basis are the capillary blood glucose levels, which are used to determine adjustments and changes in insulin dosing. CGM is an advance in technique over the standard capillary glucose measurements, but, as this study showed [1], they are very highly correlated.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Finally, the measurements that are most important to the patient on a day-by-day basis are the capillary blood glucose levels, which are used to determine adjustments and changes in insulin dosing. CGM is an advance in technique over the standard capillary glucose measurements, but, as this study showed [1], they are very highly correlated.…”
mentioning
confidence: 96%
“…In this issue, Divani et al[1] have shown that glycated albumin (GA) correlates better than hemoglobin A1c (A1c) with one week’s worth of blood glucose levels obtained by continuous glucose monitoring (CGM) in diabetic patients on hemodialysis. It should be pointed out that both were highly correlated with the CGM-obtained average glucose values (GA r = 0.884; A1c r = 0.694).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the reliability of HbA1c as a marker of glycaemic control in haemodialysis patients is questionable, given the changes in red blood cell survival and erythropoietin therapy . Continuous glucose monitoring (CGM) may offer significant benefits over traditional intermittent blood glucose testing in reducing the risks of developing long‐term complications associated with type 2 diabetes …”
Section: Introductionmentioning
confidence: 99%
“…Continuous glucose monitoring in 37 diabetic HD patients over 7 days found that levels of glycated albumin correlated better with glucose levels than did hemoglobin A1C ( r = .88 vs .69) …”
mentioning
confidence: 98%